Thermal history and comfort in a Brazilian subtropical climate: a ‘cool’ addiction hypothesis - De Vecchi, Renata (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2015)
Currently, there is a rising trend for commercial buildings to use air conditioning to provide indoor thermal comfort. This paper focuses on the impact of prolonged exposure to indoor air-conditioned environments on occupants’ thermal acceptability and preferences in a mixed-mode building in Brazil. Questionnaires were administered while indoor microclimatic measurements were carried out (i.e., air temperature, radiant air temperature, air speed and humidity). Results suggest significant differences in occupants’ thermal acceptability and cooling preferences based on thermal history; differences were found between groups based on different physical characteristics (i.e., different gender and body condition). The findings also indicated a significant potential to implement temperature fluctuations indoors when occupants are exposed to air conditioning environments in warm and humid climates.